• 1) (3+х)^2-(х^2+3^2)-3^2=0


    1 4 3 4
    2) х(х +1 -- ) + -- - -- - ( -- + х^2 )=0
    3 9 4 9

Ответы 1

  • 1)

    (3 + x) {}^{2}  - (x {}^{2}  + 3 {}^{2} ) - 3 {}^{2}  = 0 \\ 9 + 6x + x {}^{2}  - (x {}^{2}  + 9) - 9 = 0 \\ 9 + 6x + x {}^{2}  - x {}^{2}  - 9 - 9 = 0 \\ 6x - 9 = 0 \\ 6x = 9 \\ x =  \frac{ 9}{6}  \\ x =  \frac{3}{2}

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years